Pemanfaatan Natural Dyes dan Digital Marketing Pada KSM Srikandi Kreatif Pakal Surabaya Menuju Fesyen Berkelanjutan - Wiwik Handayani; Delly Nofiani; Fatimah Kalitdyah; Nur Aini Rahmaniah; Larasati Putri Kirono (LPPM ITB AAS Indonesia Surakarta, 2021)
The Covid-19 pandemic provides a lesson that it is necessary to design a business that can survive and thrive despite the dynamics of environmental change. One of the impacts of the crisis due to the pandemic is felt not only for the general public, of course it will also have an impact on the business sector, especially the creative industry. The creative industry has been predicted as an industry that is able to survive even in the crush of limited resources and environmental pressures. However, the Covid-19 pandemic which lasted for quite a long time, caused several creative industry sectors to fall. To overcome the many creative businesses that have been stopped due to the pandemic, community service activities are aimed at assisting and providing training so that they can be used for business survival. This effort is reflected in training on the use of natural dyes in making motifs on fabric media which can be processed later into various fashion products such as clothes, bags, shoes, books, etc. As well as training on the use of digital marketing to reach wider consumers by utilizing Google My Business.. The training is expected to assist business actors in creating new products so that they are able to respond to and bind consumer demand, as well as get easier product marketing with digital media.